Privatization In Eastern Germany : a Neo-institutional Analysis. - Brücker, Herbert, 1960- (Taylor & Francis Ltd., 1997)
This book gives an analysis of privatization and restructuring by the Treuhandanstalt in East Germany. It also addresses the theoretical and conceptual problems of large-scale privatization in the transformation process.